The Biocontrol and Growth-Promoting Potential of Penicillium spp. and Trichoderma spp. in Sustainable Agriculture - Wenli Sun; Mohamad Hesam Shahrajabian; Lijie Guan (Plants)
Plant-growth-promoting fungi (PGPF) play a central role in promoting sustainable agriculture by improving plant growth and resilience. The aim of this literature review is to survey the impacts of Trichoderma spp. and Penicillium spp. on various agricultural and horticultural plants. The information provided in this manuscript was obtained from randomized control experiments, review articles, and analytical studies and observations gathered from numerous literature sources such as Scopus, Google Scholar, PubMed, and Science Direct. The keywords used were the common and Latin names of various agricultural and horticultural species, fungal endophytes, plant-growth-promoting fungi, Trichoderma, Penicillium, microbial biostimulants, and biotic and abiotic stresses. Endophytic fungi refer to fungi that live in plant tissues throughout part of or the entire life cycle by starting a mutually beneficial symbiotic relationship with its host without any negative effects. They are also capable of producing compounds and a variety of bioactive components such as terpenoids, steroids, flavonoids, alkaloids, and phenolic components. Penicillium is extensively known for its production of secondary metabolites, its impact as a bioinoculant to help with crop productivity, and its effectiveness in sustainable crop production. The plant-growth-promotion effects of Trichoderma spp. are related to better absorption of mineral nutrients, enhanced morphological growth, better reproductive potential and yield, and better induction of disease resistance. Both Penicillium spp. and Trichoderma spp. are effective, affordable, safe, and eco-friendly biocontrol agents for various plant species, and they can be considered economically important microorganisms for both agricultural and horticultural sciences. The present review article aims to present the most up-to-date results and findings regarding the practical applications of two important types of PGPF, namely Penicillium spp., and Trichoderma spp., in agricultural and horticultural species, considering the mechanisms of actions of these species of fungi.